BST2/CD317 counteracts human coronavirus 229E productive infection by tethering virions at the cell surface - Wang, Shiu-Mei; Huang, Kuo-Jung; Wang, Chin-Tien (Virology (New York, N.Y.), 2014)
Bone marrow stromal antigen 2 (BST2), an interferon-inducible antiviral factor, has been shown to block the release of various enveloped viruses from cells. It has also been identified as an innate immune system component. Most enveloped viruses subject to BST2 restriction bud at the plasma membrane. Here we report our findings that (a) the production of human coronavirus 229E (HCoV-229E) progeny viruses, whose budding occurs at the ER-Golgi intermediate compartment (ERGIC), markedly decreases in the presence of BST2; and (b) BST2 knockdown expression results in enhanced HCoV-229E virion production. Electron microscopy analyses indicate that HCoV-229E virions are tethered to cell surfaces or intracellular membranes by BST2. Our results suggest that BST2 exerts a broad blocking effect against enveloped virus release, regardless of whether budding occurs at the plasma membrane or intracellular compartments. •BST2 knockdown expression results in enhanced HCoV-229E egress.•HCoV-229E virions are tethered to cell surfaces or intracellular membranes by BST2.•HCoV-229E infection at high MOI can significantly downregulate HeLa BST2 and rescue HIV-1 egress.